1959
DOI: 10.1002/jsfa.2740100507
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of meats with ionising radiations. II.—Observations on the destruction of thiamine

Abstract: In a study of the changes induced in foods by ionising radiations the destruction of thiamine in meat has been measured as one indication of chemical change. Under a given set of conditions the breakdown is related to the dose of radiation. The effect of varying the internal and external environment a t the time of irradiation has been studied. Freezing to -75" has been found to be the most effective method of preventing the destruction of thiamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1959
1959
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…The Ðndings of this work agreed with those reported previously for bacon beef liver (Williams et al 1958) chicken (Fox et al 1989 ;Hanis et al 1989), minced beef (Wilson 1959), pork (Fox et al 1989) and turkey (Thomas and Calloway 1957 ;Fox et al 1995). An increasing loss of thiamin in chicken meat was observed with increasing irradiation dose but when the irradiation treatment was carried out at freezing temperatures there was a marked reduction in the e †ects observed.…”
Section: Discussionsupporting
confidence: 93%
“…The Ðndings of this work agreed with those reported previously for bacon beef liver (Williams et al 1958) chicken (Fox et al 1989 ;Hanis et al 1989), minced beef (Wilson 1959), pork (Fox et al 1989) and turkey (Thomas and Calloway 1957 ;Fox et al 1995). An increasing loss of thiamin in chicken meat was observed with increasing irradiation dose but when the irradiation treatment was carried out at freezing temperatures there was a marked reduction in the e †ects observed.…”
Section: Discussionsupporting
confidence: 93%
“…This study has confirmed that low-temperature irradiation of bacon results in greater retention of thiamine, similar to that reported by Wilson (1959), and Thomas et al (1981) for minced beef and ground pork, respectively. This study has also identified a protective effect for thiamine when bacon is cooked before irradiation.…”
Section: Response Surface For Effect Of Frying and Final Moisture Levsupporting
confidence: 93%
“…(Thomas & Calloway, 1957), minced beef (Wilson, 1959), beef liver (Williams et al 1958) and bacon confirm that destruction of the vitamin reflects the dose applied and the conditions used during irradiation. Thiamin levels in chicken meat decrease with increasing dose but irradiation at freezing temperatures markedly reduces the effects observed (Fox et al 1989;M.…”
Section: Vitaminsmentioning
confidence: 91%